2021
DOI: 10.3390/pathophysiology28040030
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Autoimmune Male Infertility: Juxtacrine, Paracrine, and Endocrine Dysregulation

Abstract: According to global data, there is a male reproductive potential decrease. Pathogenesis of male infertility is often associated with autoimmunity towards sperm antigens essential for fertilization. Antisperm autoantibodies (ASAs) have immobilizing and cytotoxic properties, impairing spermatogenesis, causing sperm agglutination, altering spermatozoa motility and acrosomal reaction, and thus preventing ovum fertilization. Infertility diagnosis requires a mandatory check for the ASAs. The concept of the blood–tes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 123 publications
(292 reference statements)
0
8
0
Order By: Relevance
“…Previous data showed an effect of ASAs on actual DNA lack of the sperm cell. In the present study, the IgG and IgA antibodies were detected by the direct method according to their bounding with the sperm head and exhibited no significant difference for all samples and those of secondary type infertility (Chereshnev, et al, 2021). Nevertheless, significant correlations were noticed between the two classes of antibodies, IgG and IgA, which detected bounding to the sperm heads in subjects with primary type infertility (Ata, et al, 2021;Audu, et al, 2021).…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…Previous data showed an effect of ASAs on actual DNA lack of the sperm cell. In the present study, the IgG and IgA antibodies were detected by the direct method according to their bounding with the sperm head and exhibited no significant difference for all samples and those of secondary type infertility (Chereshnev, et al, 2021). Nevertheless, significant correlations were noticed between the two classes of antibodies, IgG and IgA, which detected bounding to the sperm heads in subjects with primary type infertility (Ata, et al, 2021;Audu, et al, 2021).…”
Section: Discussionmentioning
confidence: 41%
“…Conflicting evidence was observed on the relationship between the presence of ASAs and sperm characteristics including concentration, motility, and morphology in the sperm (Dacheux and Dacheux, 2014). The majority of published studies found no link between the presence of ASAs and sperm concentration or motility and morphology (Chereshnev, et al, 2021). There were No.…”
Section: Discussionmentioning
confidence: 99%
“…Paracrine of the testis is considered to be an important way to regulate spermatogenesis, and many cytokines, genes and proteins are involved in the paracrine pathway regulating spermatogenesis ( 26 29 ). In the testis, local follicle stimulating hormone, luteinizing hormone, progesterone, estradiol and progesterone are considered to be closely related to spermatogenesis ( 30 , 31 ). Comparative medicine found that the local balance between androgen and estrogen was important for spermatogenesis ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Immunological factors usually include the production of auto-anti-sperm Antibodies. Some men produce antibodies that attack their sperm, harming their fertility [1].…”
Section: Classification Of Human Infertility Conditionsmentioning
confidence: 99%